The relationship between job satisfaction and job performance of the student counselors in the city of Riyadh - Alghamdi, Ahmed Mohammed (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the relationship between job satisfaction and job performance among student counselors in the city of Riyadh, and to detect differences in the level of job satisfaction in the light of variables (experience- salary- educational qualification), as well as to detect differences in job performance in the light of the Educational stage variable. To achieve the aims of the study, the researcher used the descriptive approach, and the school counselor's satisfaction scale was the study tool that was applied to a sample of (100) student counselors from general education school in Riyadh. The results revealed that there is a positive correlation between the level of job satisfaction and the level of the job performance of student counselors in the city of Riyadh, and the results also showed that there were statistically significant differences in job satisfaction due to the variable of experience in favor of the highest experience of student counselors in Riyadh. Based on the results, the researcher suggested a number of recommendations, the most important of which were: attention to student counselors in general, and counselors with less experience in particular and work to remove of all obstacles that limit their job satisfaction.
Keywords: Job satisfaction; Job performance; Student advisors; Riyadh